A review of acellular immersion tests on bioactive glasses––influence of medium on ion release and apatite formation. (22nd January 2020) - Nommeots‐Nomm, Amy; Hupa, Leena; Rohanová, Dana; Brauer, Delia S.
Abstract: When evaluating new bioactive glass compositions for their suitability as a biomaterial, one of the first steps is the study of their behavior in contact with aqueous solutions. Ion release, pH changes, and apatite precipitation are investigated during immersion experiments, and a wide variety of solutions is used, including simulated body fluid, Tris buffer solution, various cell culture medium formulations or deionized water. This paper reviews the different parameters used for immersion experiments on bioactive glasses. Results show that, depending on solution composition, pH, and buffering capacity, the experimental outcome is likely to vary. In addition, bioactive glass particle size and solution volume/glass surface area ratio affect the resulting ion concentration in solution, and, thus, the rate at which apatite is formed. It is, therefore, important to consider these effects when planning experiments, interpreting results or comparing the results of experiments performed in different laboratories. Abstract : Investigating ion release and apatite surface layer formation during immersion in aqueous solutions is one of the first steps when characterising new bioactive glass compositions; however, results not only vary with glass composition but also with immersion conditions.